2007
DOI: 10.1038/sj.leu.2404856
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive patterns of BCL6 molecular alterations and their functional consequences in different subgroups of diffuse large B-cell lymphoma

Abstract: Gene expression profiling of diffuse large B-cell lymphoma (DLBCL) has revealed biologically and prognostically distinct subgroups: germinal center B-cell-like (GCB), activated B-celllike (ABC) and primary mediastinal (PM) DLBCL. The BCL6 gene is often translocated and/or mutated in DLBCL. Therefore, we examined the BCL6 molecular alterations in these DLBCL subgroups, and their impact on BCL6 expression and BCL6 target gene repression. BCL6 translocations at the major breakpoint region (MBR) were detected in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
136
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 52 publications
11
136
1
4
Order By: Relevance
“…[33][34][35] More recently, it was demonstrated that inactivation of TP53 was associated with a particular GEP characterized notably by a decreased expression of TRAIL receptor-2. 26 Here, we delineated approximately 100 genes that distinguish DLBCL 9p21del .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] More recently, it was demonstrated that inactivation of TP53 was associated with a particular GEP characterized notably by a decreased expression of TRAIL receptor-2. 26 Here, we delineated approximately 100 genes that distinguish DLBCL 9p21del .…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] It is more frequently detected in diffuse large B-cell lymphomas with an activated Bcell/non-germinal center B-cell phenotype than in those with a germinal center B-cell phenotype. 16,17 The significance of BCL6 gene rearrangement in disease presentation and survival is controversial. Using Southern blot analysis, Offit et al 13 Primary adrenal lymphoma A Mozos et al between BCL6 rearrangement and initial features of the disease or clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, p53 mutations are observed after chemotherapy of various hematopoietic malignancies. [50][51][52][53][54][55][56] The interactions between the p53 and Ras/Raf/MEK/ERK pathways are complex and a focal point in the sensitivity of cells to chemotherapeutic drugs such as doxorubicin. Doxorubicin, through reactive oxygen species and other molecular mechanisms, may induce p53, which in turn promotes the expression of pro-apoptotic genes, such as Noxa and Puma.…”
Section: Discussionmentioning
confidence: 99%